Impact of health plan reforms in Washington on employment decisions. (24th April 2019) - Coe, Norma B.
Abstract: The State of Washington, as part of a State Innovation Model (SIM) grant, is changing the payment model within state employee health insurance plans. The system is moving away from traditional fee-for-service reimbursement to value-based payment, through insurance design (the creation of accountable care network insurance products) and bundled payment strategies. New plans were rolled out January 2016 (enrollment occurred in late 2015), with the stated goal of getting 80% of state employees covered by plans that contain value-based purchasing within the next 5 years. The goal of payment reform is to improve member experience, member health, and cut costs. However, changing health insurance during employment can directly and indirectly change labor market outcomes. Decreasing costs of insurance could lead people to remain in the state-employment sector longer. However, it could also influence retirement timing, through changing the relative costs of insurance and through improving health. This paper examines who switches to value-based insurance, where the insurance explicitly decreases premiums without changing out-of-pocket costs. We find that the peak age for switching insurance plans is 35–45, even among the subsample of individuals who would not need to change their usual sources of care. Second, we look at the labor market activity – both leaving the state-employee sector and retiring from state-employment – and find that younger workers with value-based insurance plans are less likely to leave state employment. Further, we find evidence of value-based insurance, available at a reduced cost to both employees and retirees, leads to a shifting downward in the distribution of retirement age. While these findings support the existence of both the price and income effects, the effect sizes are rather small.